Membrane diffusing capacity and pulmonary capillary volume in rheumatoid disease. Issue 11 (November 1980) - Hills, E A; Geary, M
Abstract : In some patients with rheumatoid disease gas transfer across the lungs is abnormal. We measured the membrane component of gas transfer (Dm) and pulmonary capillary volume (Vc) in 48 patients with rheumatoid arthritis and in 48 normal volunteers matched for age, sex, and smoking habits. Volunteers had normal chest radiographs and normal forced expiratory volume in one second and vital capacity. There were no significant differences between the rheumatoid and control groups for Dm. Mean Vc in rheumatoid male smokers (64.0 ml, SD 16.5) was significantly lower than in control male smokers (76.3 ml, SD 18.0 p less than 0.05). In rheumatoid female smokers mean Vc (43.4 ml, SD 13.3) was significantly lower than in rheumatoid female non-smokers (58.4 ml, SD 15.4 p less than 0.01). There was no significant difference between rheumatoid and control female non-smokers (mean Vc 58.4 ml and 60.7 ml respectively). Significant differences in Vc in terms of per cent predicted normal were found between patients receiving corticosteroids and those not receiving corticosteroids or penicillamine (p less than 0.02) and between patients with nodules and those without (p less than 0.05). Patients with persistently low transfer factor for five years had a significantly lower Vc (p less than 0.02). There was no consistent correlation between Dm and Vc and dynamic compliance or static recoil pressure. It appears that the abnormality of transfer factor in rheumatoid disease previously demonstrated is caused by reduction of Vc. It seems that involvement of pulmonary blood vessels occurs in patients with nodules and is suppressed by treatment with corticosteroids.